Personality and lateralization in common marmosets (Callithrix jacchus) - Tomassetti, Denise; Caracciolo, Simona; Manciocco, Arianna; Chiarotti, Flavia; Vitale, Augusto; De Filippis, Bianca (Behavioural processes, 2019)
•Common marmosets present stable individual differences in personality profile.•EFA on traits shows one factor, named Inquisitiveness, accounting for 38% of the variance.•Strength of hand preference is linked to the Inquisitiveness personality factor in this species. Specialization of the left and right hemispheres to control behavioural responses may represent one of the mechanisms underlying individual differences in personality structure, as well as the preferential use of one hand. The present study investigated the relationship between personality and hand preference in common marmosets (Callithrix jacchus), a little New World monkey that presents highly consistent and stable individual hand preferences for simple reaching. To address this issue, data on 56 different behaviours from the species’ behavioural repertoire were measured in 10 different laboratory tests and during observations under social conditions on 16 adult common marmosets. Stable behavioural variables were aggregated a priori into 13 personality traits. Exploratory Factor Analysis (EFA) on personality traits was carried out to verify the presence of major personality factors, and their relationship with direction and strength of individual hand preferences was assessed by multiple regression, taking into account sex and age of the subjects. The largest number of species-specific behaviours so far investigated in this species was taken into account and robust temporal stability between two testing periods was verified. We confirm that common marmosets are characterized by specific and stable personality profiles. A single personality factor, accounting for about 38% of the total variance, was found by EFA, that describes the interest towards unusual and new experiences and resembles the human Openness domain. The strength of the hand preference was found to be predicted by this personality factor, that we named Inquisitiveness. Present results highlight common marmoset as a useful primate model for the study of the relationship between personality and lateralization.